2009
DOI: 10.1038/nature08097
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing CD8 T-cell memory by modulating fatty acid metabolism

Abstract: CD8 T cells, which play a crucial role in immunity to infection and cancer, are maintained in constant numbers, but upon antigen stimulation undergo a developmental program characterized by distinct phases encompassing the expansion and then contraction of antigen-specific effector (T E ) populations, followed by the persistence of long-lived memory (T M ) cells 1, 2 . Although this predictable pattern of CD8 T cell responses is well established, the underlying cellular mechanisms regulating the transition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
1,403
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,354 publications
(1,472 citation statements)
references
References 40 publications
48
1,403
2
8
Order By: Relevance
“…A further experiment showed that metformin treatment increased CD8 + T memory cell populations in wild-type mice, and enhanced the efficacy of anti-cancer vaccination. These intriguing findings indicate a shared mitochondrial nexus for metabolic and immune pathways, and imply that metformin may also have a direct influence upon immune competence [14].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A further experiment showed that metformin treatment increased CD8 + T memory cell populations in wild-type mice, and enhanced the efficacy of anti-cancer vaccination. These intriguing findings indicate a shared mitochondrial nexus for metabolic and immune pathways, and imply that metformin may also have a direct influence upon immune competence [14].…”
Section: Introductionmentioning
confidence: 91%
“…Another interesting mechanism for the anti-oncogenic effect of metformin has been postulated, based on the findings of a study of mice with CD8 + T lymphocytes which lack tumour necrosis factor receptor-associated factor 6 (TRAF6) and are unable to generate T memory cells [14]. This failure was associated with defective fatty acid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Proper resolution of a T cell response is as essential as its initiation because of the possible severe pathological consequences of a hyperinflammatory response. (King et al, 2006;Maitra et al, 2009;Pearce et al, 2009). For instance, TRAF6 regulates CD4 + T cell suppression by T reg cells through the PI3K (phosphatidylinositol 3-kinase)-Akt pathway (King et al, 2006), and it regulates CD8 + T cell memory development through the fatty acid metabolism pathway (Pearce et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…47 Further, it has been demonstrated that fattyacid metabolism is key to memory T-cell development and survival. 48,49 Thus, it is possible that in addition to directly regulating T-cell retention in tissues, HIC1 may also be required in T cells to promote quiescence through metabolic pathways. Future studies will aim to characterize the role for HIC1 in T-cell quiescence and memory development.…”
Section: Hic1 Is Required To Limit Stat3 Signaling In T H 17 Cellsmentioning
confidence: 99%